The Use of the Picture Exchange Communication System to Improve Expressive Language Skills in Non-Verbal Children with Autism: A Systematic Literature Review - Fahliza, Aqshal Ilham; Pradiansyah, Kevin Septia; Rhousnaka, Dika; Purwati, Ayu Endang; Firmansyah, Andan; Irpan Ali Rahman; Setiawan, Henri (Genius Journal, 2026)
Introduction: Children with non-verbal autism often experience barriers in developing expressive language skills, which impact their ability to communicate and engage in social interactions. The Picture Exchange Communication System (PECS) has been developed as an alternative intervention strategy aimed at enhancing functional communication in individuals with verbal limitations, including children with autism. Objective: Children with non-verbal autism often experience barriers in developing expressive language skills, which impact their ability to communicate and engage in social interactions. The PECS has been developed as an alternative intervention strategy aimed at enhancing functional communication in individuals with verbal limitations, including children with autism. Method: This study is a systematic review that explored seven journal databases, PubMed, ProQuest, JSTOR, Garuda, ScienceDirect, CNKI, and Wiley, from 2010 to 2024, with a population of non-verbal children with autism aged 3–12 years who received PECS intervention. The measured parameters included the number of spoken words, picture exchange ability, and functional communication. Three independent reviewers conducted screening using the PRISMA flowchart, quality assessment with the CASP Checklist, and data extraction based on author, intervention, facilitator, setting, sessions, methods, and research topics. Result: Based on 12 articles involving 158 participants, PECS was found to be effective in enhancing expressive communication in children with non-verbal autism and contributed to improvements in the use of short phrases, comprehension of instructions, as well as the reduction of non-adaptive and aggressive behaviors. PECS therapy with a duration of 30–60 minutes across 129 sessions over 23 weeks proved to be optimal, supported by RCT studies demonstrating its effectiveness in improving individuals’ expressive language abilities. Conclusion: PECS is an effective intervention for improving expressive language skills in children with non-verbal autism. This study emphasizes the importance of assessing a child’s developmental progress prior to implementing PECS, in order to tailor the intervention to individual needs. Furthermore, the active involvement of parents and educators is essential to ensure that PECS is implemented consistently and effectively across various settings.